(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article explores the significant role of artistic pedagogy in fostering the spiritual and communicative culture of student youth within modern educational systems. Artistic pedagogy, as an interdisciplinary approach, integrates elements of art, aesthetics, and pedagogy to enhance students’ personal development, emotional intelligence, and social interaction skills. The study highlights how exposure to artistic activities—such as literature, music, visual arts, and drama—contributes to the formation of moral values, cultural awareness, and communicative competence among students. Furthermore, the paper examines contemporary pedagogical strategies that employ artistic methods to create a student-centered learning environment, encouraging creativity, empathy, and critical thinking. Special attention is given to the role of higher education institutions in implementing artistic pedagogy as a tool for shaping well-rounded, socially active individuals.